2013
DOI: 10.1038/ncomms3759
|View full text |Cite
|
Sign up to set email alerts
|

Stargazin regulates AMPA receptor trafficking through adaptor protein complexes during long-term depression

Abstract: Long-term depression (LTD) underlies learning and memory in various brain regions. Although postsynaptic AMPA receptor trafficking mediates LTD, its underlying molecular mechanisms remain largely unclear. Here we show that stargazin, a transmembrane AMPA receptor regulatory protein, forms a ternary complex with adaptor proteins AP-2 and AP-3A in hippocampal neurons, depending on its phosphorylation state. Inhibiting the stargazin-AP-2 interaction disrupts NMDA-induced AMPA receptor endocytosis, and inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 46 publications
4
99
0
Order By: Relevance
“…Other possibilities include a site-specific phosphorylation code and/or a temporal sequence in serine phosphorylation. The latter is an attractive model, supported by our findings that the time-course for phosphorylation of S239/S249 and S228 in STG is different in response to chronic inactivity, and is consistent with the finding that different phosphorylation sites regulate the binding of STG to other proteins (Matsuda et al, 2013). In the future, it will be interesting to test whether phosphorylation of specific serine residues distinguishes between the two fundamentally different forms of synaptic plasticity.…”
Section: Discussionsupporting
confidence: 88%
“…Other possibilities include a site-specific phosphorylation code and/or a temporal sequence in serine phosphorylation. The latter is an attractive model, supported by our findings that the time-course for phosphorylation of S239/S249 and S228 in STG is different in response to chronic inactivity, and is consistent with the finding that different phosphorylation sites regulate the binding of STG to other proteins (Matsuda et al, 2013). In the future, it will be interesting to test whether phosphorylation of specific serine residues distinguishes between the two fundamentally different forms of synaptic plasticity.…”
Section: Discussionsupporting
confidence: 88%
“…AP-3A, which associates indirectly with AMPAR through μ3A binding to TARPs, has been implicated in the sorting and trafficking of glutamate receptors (Matsuda et al, 2013), suggesting that transcriptional upregulation of μ3A might play a critical role in synaptic scaling. As expected, immunohistochemistry localized μ3 to a number of endosomal compartments within pyramidal neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we asked whether μ3A must interact with the AP-3 complex in order to traffic GluA2 to RE. The μ3A subunit interacts with the AP-3A complex through its N terminal domain, and interacts with TARPS (and thus AMPAR) through its C terminal domain (Aguilar et al, 1997; Mardones et al, 2013; Matsuda et al, 2013). Because TTX selectively increases μ3A without increasing expression of the other AP-3 subunits, and OE of μ3A alone is sufficient to recruit AMPAR to RE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The encoding gene is targeted in the stargazer mouse (Letts et al 1998) and has been shown to be a modulator of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors at postsynaptic membranes (Tomita et al 2005;Bats et al 2007;Matsuda et al 2013). Seven different splice isoforms of the g subunit have been identified in neurons (Klugbaueret al 2000;Chen et al 2007), and, although when heterologously expressed with Ca V 2.1 (P/ Q-type) channels, they exerted effects on channel physiology (Rousset et al 2001), it is unclear whether they are genuine accessory subunits of the neuronal calcium channel complex in vivo (Ahlijanian et al 1990;McEnery et al 1991;Witcher et al 1994;Martin-Moutot et al 1995).…”
Section: Calcium Channel Structurementioning
confidence: 99%